Perencanaan Infrastruktur Teknologi Informasi di Rumah Sakit Khusus Mata Purwokerto Menggunakan Framework TOGAF - Elsa Ayunda Pratiwi; Annisa Suci Octavia; Kodir Kodir; Ito Setiawan (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
The development of information technology (IT) has had a significant impact on increasing the efficiency and quality of health services. Specialized Eye Hospitals, as facilities with specialized services, require IT infrastructure that can support medical and administrative operations optimally. The TOGAF framework (The Open Group Architecture Framework) offers a systematic approach to designing, managing and implementing effective IT architecture. This study aims to examine the application of TOGAF in IT infrastructure planning at a Special Eye Hospital. The research methods used include IT needs analysis, IT architecture modeling based on TOGAF, and evaluation of the architecture implementation. The research results show that the application of TOGAF is able to increase operational efficiency, speed up access to patient information, and improve overall service quality. This research contributes to providing practical guidance for other hospitals wishing to optimize their IT systems using the TOGAF approach.